PENERAPAN MODEL TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI SIFAT- SIFAT BANGUN RUANG - Budianti, Yudi; Tasrif, Arrahim; Budiati, Diah Rahmawati (PD PGMI se Indonesia, 2022)
Mathematics is an educational content that has a high impact and can be applied in everyday life. Learning takes place at all levels of education, from elementary school to university. Problems in learning mathematics, especially in elementary schools, are caused by passive student activity and low learning outcomes. The purpose of this study is to examine solving problems in learning mathematics using innovative learning implementations. The process of data analysis with the process of reviewing the literature of several journals concludes that learning mathematics using the Two Stay Two Stray (TSTS) cooperative model can improve student learning outcomes and student activity. The Two Stay Two Stray (TSTS) learning model students are able to overcome learning problems that are individualistic and students lack self-confidence in conveying the information they know, so that afterwards students are able to be more confident and able to help other students get rid of fear of mathematics and lead to increased achievement of results student learning is better and more effective compared to other learning models, especially by maximizing the three aspects of learning outcomes, namely cognitive, affective and psychomotor aspects.